Analyzing of Hopper Nozzle Vibrator System of Low Frequency Direct-Write Deposition. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Vibration assisted flow deposition method has great potential to be applied on layer manufacturing processes. Generally it uses hopper and nozzle which placed on a vibrator mechanism. Vibration assisted flow with low frequency (70-120 Hz) attached to pulse generator can be inexpensively made by electromagnetic system. The focus of this research is to analyze the influence of pulse generator position on beam construction toward powder flow-ability. Due to the limitation of measurement tools, determining of amplitude was approached by numerical analysis with a Finite Element Analysis Software, and then the biggest value of amplitude resulting by numerical analysis was then compared with measurement value by optical microscope. The different value (by numerical analysis and by measurement) was used as load constant value when determine lower amplitudes. The Amplitude data, which resulted by numerical analysis, were variated with frequency to get powder flow-ability characteristic and use to line deposition testing. This flow-ability experiment used stainless steel powder 52-75 gm in diameter, and 75-150 gm for line deposition experiment. The numerical analysis results showed that closer position of pulse generator to hopper nozzle yields the greater amplitude and lengthens the range of flow-ability frequency. Double beams were recommended due to the ability to produce the narrow line width compared with a single beam.